2004
DOI: 10.1128/jb.186.12.3991-3999.2004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the SppA1 Peptidase in Acclimation to Saturating Light Intensities in Synechocystis sp. Strain PCC 6803

Abstract: The sll1703 gene, encoding an Arabidopsis homologue of the thylakoid membrane-associated SppA peptidase, was inactivated by interposon mutagenesis in Synechocystis sp. strain PCC 6803. Upon acclimation from a light intensity of 50 to 150 E m ؊2 s ؊1 , the mutant preserved most of its phycobilisome content, whereas the wild-type strain developed a bleaching phenotype due to the loss of about 40% of its phycobiliproteins. Using in vivo and in vitro experiments, we demonstrate that the ⌬sppA1 strain does not unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…At intensities greater than 10 W m −2 , a significant increase in photocurrent was not observed. We note that, although perhaps coincidental, this intensity is nearly identical to that under which the cyanobacterial culture was grown, a value chosen because it corresponds to light saturated but not photoinhibited growth for Synechocystis [29]. Photocurrent magnitude was not the only parameter directly dependent on light intensity.…”
Section: Resultsmentioning
confidence: 79%
“…At intensities greater than 10 W m −2 , a significant increase in photocurrent was not observed. We note that, although perhaps coincidental, this intensity is nearly identical to that under which the cyanobacterial culture was grown, a value chosen because it corresponds to light saturated but not photoinhibited growth for Synechocystis [29]. Photocurrent magnitude was not the only parameter directly dependent on light intensity.…”
Section: Resultsmentioning
confidence: 79%
“…However, the role of NblA upon HL acclimation has not been examined. Pojidaeva et al (2004) reported that the SppA1 peptidase encoded by sll1703 cleaves the distal linker protein L R 33 and the membrane linker L CM 99 when exposed to increasing photon flux densities. Degradation of L R 33 and L CM 99 would account for both a shortening of PBS rods and a release of PBS from the membranes.…”
Section: Phycobilisomementioning
confidence: 99%
“…This dual function implies specific regulation for assembling, disassembling, and remodeling the PBS structure according to changes in metabolic and energy requirements. Cyanobacteria have evolved several molecular mechanisms for acclimation of the PBS antenna that operates at the transcriptional (4,5), translational, and posttranslational levels (6,7). Taken together, these regulatory mechanisms contribute to remodeling PBS composition, size, and number per thylakoid membrane when cells are exposed to environmental changes.…”
Section: Phycobilisomes (Pbss)mentioning
confidence: 99%
“…Acclimation to higher light intensities as well as nitrogen deprivation induces a down-sizing of the PBS antenna that is due in part to changes in PBS gene expression (4,5) and in part to proteolytic processes that target some PBS subunits (6,7). In particular, protease SppA1 causes the cleavage of linker proteins under acclimation to higher light regimes with the subsequent release of distal PC rod segments (7). Indeed, we observed that the rate of linker protein phosphorylation decreased with environmental cues that cause restructuring, disassembly, and degradation of PBSs.…”
Section: Dephosphorylation Of Pbs Linkers Is Enhanced Under High Lighmentioning
confidence: 99%